Pengaruh Profitabilitas, Ukuran Perusahaan, Umur Perusahaan, Ukuran KAP, dan Opini Audit Terhadap Audit Report Lag (studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2016-2018) - Muhammad Fikri Hendrawan; Trisninik Ratih Wulandari (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2020)
Audit report lag is the time span between the date of the financial statements until the completion of fieldwork. Financial statements must be published in a timely manner, because the information is very relevant in decision making. This study is intended to analyze the impact of company size, profitability, company age, audit opinion and KAP size on audit report lag in Manufacturing companies listed on the Indonesian Stock Exchange in 2016-2018. The data used consisted of 288 samples. The analytical method used is using multiple linear regression analysis. The results obtained are audit report lag influenced by profitability and age of the company, but not influenced by KAP size, company size, and audit opinion.